Apolipoproten B , LDL Kolesterol dan apoB / apoA -I Rasio Pasien Angina Stabil - Olivia Handayani; Djanggan Sargowo (The Indonesian Heart Association, 2016)
Aim: To acknowledge the nature of correlation between apolipoprotein B concentrations and LDL cholesterol levels in patients with stable angina pectoris and also to show that the ratio of apoB/apoA-I may be a promising predictor for the risk of cardiovascular disease.Methods: This is an observational study with cross-sectional approach of 34 patients with stable angina pectoris. Prior to the study, patients were advised to fast for 10-12 hours and must complete the informed consent. Patients underwent physical examination and anthropometric measurements (height, body weight, waist circumference), blood test, and ECG check.Results: From 34 patients, the prevalence of high levels of total cholesterol (>200 mg/dl) in men and women are 45.5% and 47.8%, respectively; and 90.9% men and 87% women with increased LDL-C (?100 mg/dl). Low value of apoA-I was determined in 5 men (45.5%) and 4 women (17.4%); and high value of apoB was found in 7 men (63.6%) and 11 women (47.8%), whereas 13 subjects with unfavorable apoB/apoA-I ratio. Six subjects had low levels of apoA-I along with high levels of apoB. ApoB/apoA-I ratio above 0.9 was found in 6 or 11 men (54.5%) and 7 of 23 women (30.4%).Conclusion: We found that in 34 patients with stable angina, 18 of them (52.9%) showed high plasma apoB concentration. This is parallel to 30 subjects (88.2%) with high LDL cholesterol levels, and also 13 subjects (38.2%) with high apoB/apoA-I ratio. It can be concluded the higher the ratio of apoB to apoA-I, the greater the risk of cardiovascular disease. Lifestyle management and pharmacological intervention in dyslipidemia is important in reduction of cardiovascular events.